Retour sur les relations entre les principes de solidarité et de confiance mutuelle à la lumière des droits fondamentaux - Marion Fontaine (Revista Vasca de Administración Pública, 2024)
The growing use of the concept of ¿solidarity¿ in institutional and political discourse attests that the ¿refugee crisis¿ is first and foremost a crisis of solidarity in the European Union. More broadly, it reveals a crisis of values that questions mutual trust between Member States. This article examines the law and legal practice to analyze the nature of the relationship between the principles of ¿solidarity¿ and ¿mutual trust¿. The latter are structural principles of the Union, as illustrated by the fundamental rights litigation concerning asylum and the European Arrest Warrant. Indeed, the diptych of solidarity and trust is identifiable in these two areas of the AFSJ, and the interaction and resolution of their relationship is closely linked to the imperative of protection of fundamental rights.